نظام القانون المدني وعلقاته بتطوير النظام الاقتصادي الإسلامي بإندونيسيا ‏ - Nurul Azizah (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2023)
Indonesia adheres to a civil law system. However, in reality, several regulations in Indonesia are derived from Islamic law (Sharia) and customary law, which are part of the common law system. This article will discuss the relationship between the current civil law system in Indonesia and its connection to Islamic economic law in Indonesia, influenced by the common law system. The curriculum used for this study is the normative legal curriculum, with Indonesian legislation as the primary source of analysis. The result of this research indicates that civil law in Indonesia today does not appear to be purely civil law, as Indonesia draws from many sources, including customary law and Islamic law. Islamic law is a clear example of legislation in Indonesia that is adopted from the common law system, such as laws regarding marriage, endowments, and others. Many regulations stem from Islamic law, although they mainly serve as guidelines for judges in resolving family law disputes within the realm of Sharia economic matters. The implementation of Islamic Economic Law (KHES) by the Supreme Court Regulation No. 2 of 2008 is evidence of the connection between Indonesian law and Islamic Sharia, even from other countries. Some of its principles are derived from the Code of Justice, which was applied as the official law of the Ottoman Empire.